P154 EVOLUTION OF ECHOCARDIOGRAPHIC AND CARDIAC MRI ABNORMALITIES DURING FOLLOW–UP IN PATIENTS WITH PREVIOUS MIS–C DIAGNOSIS. (18th May 2022) - Sirico, D; Basso, A; Sabatino, J; Reffo, E; Cavaliere, A; Biffanti, R; Cerutti, A; Castaldi, B; Zulian, F; Da Dalt, L; Di Salvo, G
Abstract: Background: Cardiovascular manifestations in the acute phase of MIS–C are frequent. However, there is lacking evidence regarding late cardiological follow–up of this cohort of patients. The aim of our study was to describe the early and late cardiac abnormalities in patients with MIS–C, assessed by standard echocardiography (TTE), speckle tracking echocardiography (STE), and cardiac MRI (CMR). Materials and Methods: 32 consecutive patients with confirmed MIS–C diagnosis were enrolled in this study. Clinical, laboratory and microbiological data were collected for all patients. At disease onset, all children underwent standard transthoracic echocardiography, STE with analysis of left ventricle global longitudinal strain (GLS) and 23 (75%) of them performed CMR. Patients underwent complete cardiological evaluation, including echocardiography and STE at two months (T1) and six months (T2) after diagnosis. CMR was repeated at six months after diagnosis. Results: Mean age was 8.25±4years (range 1.3–17.7). Cardiovascular symptoms were present in 45.8% of cases. Thirteen children (40.6%) shared Kawasaki Disease–like symptoms, and 5 (15.6%) needed ICU admission. All patients showed an hyperinflammatory state. Tn–I was elevated in 20 (62.5%) and BNP in 28 (87.5%) patients. Median time to STE evaluation was 7 days and to CMR 18 days since fever onset. Mean LVEF at baseline was 58.8±10% with 10 patients (31%) below 55%. STE showed reduced mean LV GLS (–17.4±4%). Coronary dilation was observed in 9 (28, 1%) patients. On CMR, LGE with nonischemic pattern was evident in 8/23 patients (35%). Median time to T1 and T2 evaluation was respectively 48.5 and 207 days. Follow–up data showed statistically significant improvement in left ventricular systolic function compared to acute phase. LVEF improved rapidly at T1 (62.5 ± 7.5 vs. 58.8±10.6%, p value 0.044) with only three patients (10%) below ≤ 55% at T1 and one patient (4%) at T2. LV GLS remained impaired at T1 (–17.2 ± 2.7 vs.–17.4 ± 4, p value 0.71), and significantly improved at T2 (–19±2.6% vs. –17.4±4%, p value 0.009). LV GLS was impaired (>–18%) in 53% of patients at baseline and T1, while only 13% showed LV GLS reduction at T2. CMR, performed 6 months after diagnosis, showed LGE persistence in 33.4% of cases. Conclusions: Even though, early cardiac involvement significantly improves during follow–up, subclinical myocardial damage seems to be still detectable 6 months follow up in one third of MIS–C patients.